Relation Between Dietary Carotenoid Intake, Serum Concentration, and Mortality Risk of CKD Patients Among US Adults: National Health and Nutrition Examination Survey 2001–2014 - Hu, Yuncan; Cai, Xiaoyu; Zhang, Nanhui; Li, Yu; Mao, Ya; Ge, Shuwang; Yao, Ying; Gao, Hui (Frontiers in Medicine, 2022)
Background: Current evidence on the relationship between carotenoids and chronic kidney disease (CKD) patients are limited and controversial. Methods: Data were obtained from the Nutrition and Health Examination Survey (NHANES) database and the NHANES Linked Mortality File, both from a nationally representative sample. Dietary intake was assessed through 24-h dietary recall, and information was available both on dietary and serum α-carotene, β-carotene, β-cryptoxanthin, lycopene, and lutein/zeaxanthin (combined) through the NHANES cycles used. We used multivariable Cox proportional hazards regression models to estimate the risk for all-cause mortality associated with carotene intakes and serum levels, adjusting for potential confounding factors. Results: Of the 6095 CKD participants, 1924 subjects died (mean follow-up time, 8.1years). After eliminating all the confounding factors, we found that high levels of total carotene (HR = 0.85, 95% CI, 0.75-0.97, P = 0.011) intakes at baseline were significantly associated with a lower risk of death. And the serum concentrations of carotenoid were also showing that a-carotene (HR = 0.77, 95%CI, 0.65-0.92, P = 0.002), beta-cryptoxanthin (HR = 0.83, 95%CI, 0.70-0.98, P = 0.019), lycopene ( (HR = 0.77, 95% CI, 0.65-0.91, P = 0.002), and lutein + zeaxanthin ( (HR = 0.82, 95% CI, 0.70-0.96, P = 0.002) was significantly associated with decreased all-cause mortality of CKD patients. The associations remained similar in the sensitivity analyses. Conclusion: Findings suggest that high-level carotene dietary intake and the serum concentration were associated with a lower risk of mortality in the CKD population.